1980
DOI: 10.1287/opre.28.6.1385
|View full text |Cite
|
Sign up to set email alerts
|

A Maxmin Location Problem

Abstract: The problem considered is to locate a point in a given convex polyhedron which maximizes the minimum Euclidean distance from a given set of points. The paper describes several possible application areas and shows the existence of a finite set of candidates for the optimal solution. A combinatorial algorithm is presented for the problem in three dimensions, and it is compared with existing nonconvex programming algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 14 publications
0
37
0
Order By: Relevance
“…First attempts to solve location problems with such undesirable facilities appeared in the 1970's [4,6,17]. Algorithms based on a DC formulation are presented for instance in [3,9,31,40].…”
Section: Application and Numerical Resultsmentioning
confidence: 99%
“…First attempts to solve location problems with such undesirable facilities appeared in the 1970's [4,6,17]. Algorithms based on a DC formulation are presented for instance in [3,9,31,40].…”
Section: Application and Numerical Resultsmentioning
confidence: 99%
“…If appropriate probabilistic assumptions about underlying error distributions are made, least squares produces what is known as the maximum-likelihood estimate parameters. Even if the probabilistic assumptions are not satisfied, research in this areas has shown that least squares produces useful results [1,2,5,6,7,8,9,10,11,14,15,19,21,22,23,24,25,26] A very common source of least squares is curve fitting. Let x be the independent variable and let y  x denote an unknown function of x that we want to approximate.…”
Section: Optimal Designmentioning
confidence: 99%
“…There are numerous publications where facility location problems have been discussed [4,5,8,9,10,13,14,15,17,19,20,21,22,23].The problem has given rise to extraordinary number of generalizations, extensions and modifications. It would literally require volumes to do them justice; space only permits only a brief and somewhat arbitrarily selected summary.…”
Section: Location Theorymentioning
confidence: 99%
“…The solution is found by constructing the Voronoi diagram for the set of points. The first papers on the maximin location problem were published five years later by Dasarathy and White (1980) and .Building on their earlier work on pattern recognition, Dasarathy and White (1980) first formulated and solved the maximin problem with Euclidean distances for a feasible region, which is a convex polyhedron in k-dimensional space. They delineated their general algorithm for a 3-dimensional space.…”
mentioning
confidence: 99%
“…Although there were no apparent customers, the optimization approach-similar to the geometrical approach of Shamos and Hoey (1975)-suggests that the customers constitute an infinite set represented by the boundaries of the protected areas. The solution amounts to finding the largest (empty) circle that contains no points of the protected areas yet whose center is in S.Melachrinoudis and Smith (1995) extended the Voronoi method of Dasarathy and White (1980) and developed an O( mn 2 ) algorithm for the weighted maximin problem. For two points a k , a ℓ having weights w k , w ℓ such that w k > w ℓ , the loci of weighted equidistant points is the Apollonius circle.…”
mentioning
confidence: 99%